Diagnostic Stability of Acute and Transient Psychotic Disorders in Patients Attending Tertiary Care Hospital - Ranjan, Sanjeev; Shakya, R; Shyangwa, P M (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Acute and Transient Psychotic Disorders (ATPDs) have been the subject of nosological debate. Some authors argue that these conditions should be considered as an independent group of disorders. Others view these psychoses as variants of schizophrenia or mood disorders, pointing to their diagnostic instability. There have been few studies of the diagnostic stability based on the International Classification of Diseases-tenth edition (ICD-10) category of ATPDs, and these studies have mixed results. This study was done to examine the diagnostic stability of ATPDs according to ICD-10. MATERIAL AND METHODS: Thirty patients diagnosed as ATPDs at psychiatry department of B.P. Koirala Institute of Health Science (BPKIHS) were followed up at one month and after three months of their onset of illness. Their diagnosis was reassessed at every follow-up using standard instrument. RESULTS: The diagnosis of ATPDs was unchanged in twenty four (80%) out of thirty patients. Diagnostic change was to schizophrenia in three cases and to mood disorders in three other cases. CONCLUSION: Overall, ATPDs is a diagnostically stable entity. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12035 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08, Page: 7-10